Student mathematical communication capability improvement using the metacognitive strategy - W O Dahiana; T Herman; R Nirawati (Pascasarjana Universitas Pendidikan Indonesia, 2020)
This study aims to determine the improvement of students' mathematical communication skills using metacognitive strategies. The method used was quasi-experimental with a non-randomized control group post-test control group design. The sample of this study was the junior high school students of class VIIA and VIIB as experimental and control classes with many students in each class 19 and 17 people. The instrument used was a test of mathematical communication skills. The results showed that students' mathematical communication skills using metacognitive strategies were better than students who used conventional learning. Thus the metacognitive strategy can be used as an alternative strategy to improve students' mathematical communication skills.